Pengaruh Media Whatsapp Dan Leaflet Terhadap Perilaku Pemeriksaan Payudara Sendiri Pada Siswi Sekolah Menengah Atas Di Kota Kendari - Putu Suri Saraswati; Tasnim Tasnim; Sunarsih Sunarsih (Al-Sihah : The Public Health Science Journal, 2019)
The low of teens in doing Breast Self-examination (BSE) can be motivated by the lack of knowledge on how to perform BSE. An effort to improve the BSE behavior is health education. This study aims to determine the effect of health education with whatsapp and leaflets against BSE behavior at high school in Kendari. This study is a quasi-experimental with pre-post test control group design. The population was student with a sample of 39 students divided into two experimental groups and one control group. Sampling was done by cluster systematic random sampling. Result shows the differences in knowledge, attitudes and practices of each and between groups. Knowledge has overall increased since the first intervention by whatsapp and the second intervention by leaflet. Attitudes and practices have been steadily increasing in each group. The end of measurement all group had good knowledge and attitudes of BSE. In practices, whatsapp group was 100% able to perform BSE, leaflet group was 53.8% and control group was 23.1%. The conclusions there are differences in knowledge, attitudes and practices of each and among groups. Whatsapp become the effective media to improve the knowledge and practice. Leaflet and whatsapp media are equally effective in improving attitude of BSE at high school in Kendari.Keywords : Behavior, Breast Self-examination, leaflets, whatsapp